Janus Kinase Inhibitors and Cell Therapy - Assal, Amer; Mapara, Markus Y. (Frontiers in Immunology, 2021)
Cellular therapies such as allogeneic hematopoietic stem cell transplantation (HSCT) and immune-effector cell therapy (IECT) continue to have a critical role in the treatment of patients with high risk malignancies and hematologic conditions. These therapies are also associated with inflammatory conditions such as graft-versus-host disease (GVHD) and cytokine release syndrome (CRS) which contribute significantly to the morbidity and mortality associated with these therapies. Recent advances in our understanding of the immunological mechanisms that underly GVHD and CRS highlight an important role for Janus kinases (JAK). JAK pathways are important for the signaling of several cytokines and are involved in the activation and proliferation of several immune cell subsets. In this review, we provide an overview of the preclinical and clinical evidence supporting the use of JAK inhibitors for acute and chronic GVHD and CRS.